Case Report: Percoronary device occlusion of right coronary artery fistula into left ventricle in an infant - Sun, Shi-Bin; Pai, Run-Tian; Wang, Heng-Bao; Farhaj, Zeeshan; Xiao, Yilei; Hongxin, Li (Frontiers in Cardiovascular Medicine, 2025)
A 4-month-old male infant (weight 6 kg, height 67 cm) with heart failure was diagnosed with an isolated 8.9 mm right coronary artery fistula draining into the left ventricle (LV), identified via transthoracic echocardiography and computed tomography angiography. The large, tortuous, and aneurysmal fistula was treated using a minimally invasive percoronary approach, avoiding the high risks of surgery and the challenges of percutaneous closure. A 10 mm muscular ventricular septal occluder was deployed successfully. At 3 months, imaging showed reduced LV size, excellent device positioning, and complete fistula occlusion without thrombus formation. By 6 months, optimal remodeling was confirmed. Over 10 years of follow-up, the patient’s troponin I levels and electrocardiograms remained normal, with no ST-T abnormalities.